Roads in the rainforests: Legacy of selective logging in Central Africa - (:unkn) unknown (My University, 2016)
Selective logging prevails in tropical forests around the world, posing urgent questions about how to reconcile timber extraction with biodiversity conservation. Roads are those elements of selective logging that are most costly, most visible and they probably have the most far-reaching environmental impacts. While many studies have outlined road related threats to forest ecosystems, little is known about the persistence of logging roads in the forest landscape. This is especially important in Central Africa, where selective logging is the most important type of land use, both in terms of spatial extent and financial yield. In this thesis I analyze the temporal and spatial dynamics of logging road networks in a part of the Congo Basin and apply these findings to make suggestions for forest management. In five chapters I am approaching the subject from different angles and on different scales:In the introductory chapter, I compare the content and the orientation of scientific literature on logging roads in tropical forests. In general I identified two strains in the literature, one focusing specifically on road related impacts on forest ecosystems and the other giving technical advice in road planning, building and maintenance in order to improve efficiency and reduce impacts. A third, partially distinct direction of research is oriented on the characterization of the spatial distribution and coverage of forest road networks on larger scale to monitor forest exploitation and related degradation.The second chapter presents a methodology to identify roads in Central African forests based on remote sensing with LANDSAT images. In a time series approach, I used survival analysis to evaluate the temporal dynamics of secondary logging roads over the last 30 years and showed how road persistence differs depending on environmental variables such as geological substrates.The third chapter approaches the persistence of logging roads from a field based perspective
Keywords: African Research